Neuroprotection and anti-seizure effects of levetiracetam in a rat model of penetrating ballistic-like brain injury - Caudle, Krista L.; Lu, Xi-Chun M.; Mountney, Andrea; Shear, Deborah A.; Tortella, Frank C. (Restorative neurology and neuroscience, 2016)
Purpose: We assessed the therapeutic efficacy of FDA-approved anti-epileptic drug Levetiracetam (LEV) to reduce post-traumatic nonconvulsive seizure (NCS) activity and promote neurobehavioral recovery following 10% frontal penetrating ballistic-like brain injury (PBBI) in male Sprague-Dawley rats. Methods: Experiment 1 anti-seizure study: 50 mg/kg LEV (25 mg/kg maintenance doses) was given twice daily for 3 days (LEV3D) following PBBI; outcome measures included seizures incidence, frequency, duration, and onset. Experiment 2 neuroprotection studies: 50 mg/kg LEV was given twice daily for either 3 (LEV3D) or 10 days (LEV10D) post-injury; outcome measures include motor (rotarod) and cognitive (water maze) functions. Results: LEV3D treatment attenuated seizure activity with significant reductions in NCS incidence (54%), frequency, duration, and delayed latency to seizure onset compared to vehicle treatment. LEV3D treatment failed to improve cognitive or motor performance; however extending the dosing regimen through 10 days post-injury afforded significant neuroprotective benefit. Animals treated with the extended LEV10D dosing regimen showed a twofold improvement in rotarod task latency to fall as well as significantly improved spatial learning performance (24%) in the MWM task. Conclusions: These findings support the dual anti- seizure and neuroprotective role of LEV, but more importantly identify the importance of an extended dosing protocol which was specific to the therapeutic targets studied.